Deformation and breakup of water droplets containing polymer under a DC electric field. Issue 10 (11th June 2022) - Huang, Xin; Luo, Xiaoming; Han, Yunrui; Li, Weidong; Lai, Yuekun; Teng, Lin
Abstract: The deformation and breakup behaviors of droplets containing polymer are investigated by high‐speed photography to reveal the mechanism of electric field collapse when treating the emulsion containing polymer. The results show the electric field collapse process caused by droplet breakup consists of three steps. First, the droplet containing polymer ejects liquid filament under strong electric field. Second, the liquid filament is continuously stretched until it touches positive and negative electrodes. Finally, the severe Joule heating effect appears because the strong electric current flows through the liquid filament. The release of a large amount of heat causes the formation, expansion, and collapse of bubble, resulting in the fracture of liquid filament and the collapse of electric field. The increase of polymer concentration strengthens the Joule heating effect and enlarges the influence scope of bubble expansion and collapse. These findings provide significant guidance for the stable operation of electric dehydrator.